Anterior Cervical Discectomy and Fusion in the Outpatient Ambulatory Surgery Setting: Analysis of 2000 Consecutive Cases. Issue 7 (16th November 2020) - McGirt, Matthew J; Rossi, Vincent; Peters, David; Dyer, Hunter; Coric, Domagoj; Asher, Anthony L; Pfortmiller, Deborah; Adamson, Tim
Graphical Abstract: